Real-time thermal expansion measurement system and the data acquisition and control application software - User interface - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2003)
In order to operate the designed thermal expansion measurement system, a user interface is constructed by using Borland Delphi. This paper presents how the user interface constructed and why it is necessary. © 2003 IEEE.
Keywords: Application software; Control systems; Data acquisition; Monitoring; Programming profession; Real time systems; Software measurement; Temperature; Thermal expansion; User interfaces